Pengenalan Aplikasi Kipin School Sebagai Upaya Meningkatkan Inovasi Pembelajaran Berbasis Digital di SDN 22 Tondongkura - Ansyari, Ilman Indra; Razak, Firdha; Alam, Aztri Fithrayani; Rasmi, Rasmi; Munira, Munira; Fadillah, Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
SDN 22 Tondongkura in Pangkep Regency, South Sulawesi, still relies on conventional teaching methods with limited utilization of digital technology. To improve learning quality, a Community Service Program (Community Outreach) was implemented with the aim of integrating the Kipin School application into the teaching and learning process. This two-day program involved interactive training combining lectures, discussions, hands-on practice using the application, and classroom observations to provide constructive feedback. Despite technical challenges such as unstable internet connectivity and limited device specifications, evaluation results showed a significant improvement in teachers' ability to utilize the application's features, including educational videos and interactive exercises. The increase in teachers’ confidence and enthusiasm in adopting this technology was also supported by the full commitment of the school principal. These findings indicate that the implementation of the Kipin School application is effective in enhancing the quality of learning at SDN 22 Tondongkura. However, the sustainability of the program requires improvements in technological infrastructure and ongoing training for educators to ensure optimal and sustainable use of digital technology in the learning process.